Pengaruh Pemasangan Bangunan Peninggi Muka Air (Subweir) Terhadap Gerusan yang Terjadi di Hilir Bendung - Pudyono, Pudyono (Rekayasa Sipil, 2010)
This research used the dam model from the prototype of the Bakalan Dam in the Kecamatan WagirKabupaten Malang with the 1 : 30 scale as the case of the study. In this model research, in the damdownstream was formed as the moveable bed with the mixing of sand (50%) and the gravel (50% sieve 10mm), with the three discharge variation Q = 6 liter/sec, 9 liter/sec and 12 liter/sec.The aim of this research is finding out the minimum scouring depth occurrence in the downstreamof the dam with the subweir installment. The height variation of the sub weir was Zo = 0; Z1 = 1,66cm; Z2 = 3,33 cm; and Z3 = 5 cm, and the variation of length sub weir installment range in the downstreamof the dam was L1 = 60 cm; L2 = 75 cm; L3 = 90 cm.The result of this research was shown that the minimum downstream dam scouring was occurredfor discharge variation range Q1 = 6 litter/sec until Q2 = 9 litter/sec with the variation of the length subweir installment was 60 cm until 75 cm from the toe of the dam that used the 5 cm of the sub weir height.While for the discharge in the range of Q2 = 9 litter/sec to Q3 = 12 litter/sec with the all of the length ofinstallment and the height of sub weir variation have not gave the significance influence for the depth ofscouring. Its shown that that trend of the scouring depth was followed the trend of the discharge without thesub weir installment (Zo). It is mean hat for the high discharge, installation of the sub weir was having notinfluence to decrease the scouring depth of the downstream dam.Â